Kearifan Lokal dalam Novel Dhalang Mbarang Katresnan Karya Tulus Setiyadi (Sebuah Kajian Antropologi Sastra) - Munna, Fauzzul; Sulaksono, Djoko; Rahmat, Rahmat (Universitas Sebelas Maret, 2022)
This research is motivated by the disclosure of the values of Javanese local cultural wisdom in a novel which has positive influences on its readers. The novel Dhalang Mbarang Katresnan by Tulus Setiyadi as one of the novels that contain local cultural wisdom is part of cultural documentation. Therefore, this study uses literary anthropology as an assessment tool. The purpose of this study is to explain the local wisdom of Javanese culture in the novel Dhalang Mbarang Katresnan by Tulus Setyadi. The research method used in this research is descriptive-qualitative method. In this research, the data is the result of document analysis, and the data source is from the document. The sampling technique used in this research is the purposive sampling technique. The data collection in this study used document data assessment techniques. The results of this study indicate that there are two forms of local wisdom of Javanese culture. The first is local wisdom in the form of abstract values or norms that are beneficial if applied in everyday life. Second, there is objective local wisdom in the form of objects that can be seen.